DEVELOPMENT OF ACCELERATING STRATEGY ON IMPROVEMENT OF STUDY PROGRAM ACCREDITATION IN ACCORDANCE WITH 9 CRITERIAS OF BAN-PT IN THE STATE UNIVERSITY OF MEDAN - Panggabean, Deo Demonta; Motlan; Harahap, Mukti Hamjah; Irfandi; Sirait, Albert Pauli (Advances in Social Sciences Research Journal, 2020)
This study aims to develop a strategy to speed improvements accreditation at the State University of Medan. This research is a development (Research and Development / R & D) with BMVIT policy development cycle. Data was collected using response sheets, questionnaires and questionnaires. The results obtained through this research are: 1) the target accreditation courses that will expire next year is ranked accreditation excellent, 2) the factors inhibiting the acceleration of accreditation in Study Program State University of Medan, among others: (a) a system that can be used to ease the study program to access the data; (B) The level of understanding of each course with the new accreditation system is still low; (C) The lack of assistance in preparing the study program accreditation instruments, while the supporting factors accelerating the increase in Study Program accreditation State University of Medan, among others: (a) Participation of the entire community of course is very good; (B) the infrastructure owned by their respective study program has been very adequate, 3) Strategy accelerated increase in Study Program accreditation State University of Medan, among others: (a). Perception related to the new accreditation system in stages; (B) Assistance study program in a sustainable and measurable; (C) Preparation of system data relating to the needs of accreditation instruments that can be accessed by programs with ease. while the supporting factors accelerating the increase in Study Program accreditation State University of Medan, among others: (a) Participation of the entire community of course is very good; (B) the infrastructure owned by their respective study program has been very adequate, 3) Strategy accelerated increase in Study Program accreditation State University of Medan, among others: (a). Perception related to the new accreditation system in stages; (B) Assistance study program in a sustainable and measurable; (C) Preparation of system data relating to the needs of accreditation instruments that can be accessed by programs with ease. while the supporting factors accelerating the increase in Study Program accreditation State University of Medan, among others: (a) Participation of the entire community of course is very good; (B) the infrastructure owned by their respective study program has been very adequate, 3) Strategy accelerated increase in Study Program accreditation State University of Medan, among others: (a). Perception related to the new accreditation system in stages; (B) Assistance study program in a sustainable and measurable; (C) Preparation of system data relating to the needs of accreditation instruments that can be accessed by programs with ease. 3) Strategies accelerated increase in Study Program accreditation State University of Medan, among others: (a). Perception related to the new accreditation system in stages; (B) Assistance study program in a sustainable and measurable; (C) Preparation of system data relating to the needs of accreditation instruments that can be accessed by programs with ease. 3) The accelerated Strategies to increase accreditation of all study Programs in State University of Medan, among others: (a). Perception related to the new accreditation system in stages; (B) Assistance study program in a sustainable and measurable; (C) Preparation of system data relating to the needs of accreditation instruments that can be accessed by programs with ease.